Frequency of Fecal Carriage of ESBL Resistance Genes in Multidrug-Resistant Pseudomonas aeruginosa Isolates from Cancer Patients at Laquintinie Hospital, Douala, Littoral Region, Cameroon - Michael F. Kengne; Armelle T. Mbaveng; Ousenu Karimo; Ballue S. T. Dadjo; Ornella D. Tsobeng; Wiliane J. T. Marbou; Victor Kuete (International Journal of Microbiology)
Background. Opportunistic infections are the second cause of death among cancer patients. This study aimed at determining the antimicrobial profile and the prevalence of extended-spectrum beta-lactamase (ESBL)-gene carriage of Pseudomonas aeruginosa isolates among cancer patients at the Douala Laquintinie Hospital, Littoral Region of Cameroon. Between October 2021 and March 2023, 507 study participants were recruited among whom 307 (60.55%) were cancer patients, compared to 200 (39.45%) noncancer patients. Fifty-eight P. aeruginosa isolates were isolated from fecal samples of forty-five cancer patients and thirteen noncancer patients using Cetrimide agar. The antimicrobial resistance profile of the isolates was determined using the Kirby–Bauer disk diffusion method. The polymerase chain reaction was used to detect the presence of extended-spectrum beta-lactamase genes among P. aeruginosa isolates. P. aeruginosa showed significant resistance rates in cancer patients compared to noncancer patients to imipenem, cefotaxime, and ceftazidime, piperacillin-tazobactam, ticarcillin-clavulanic acid, and ciprofloxacin. The multidrug resistance (MDR) rate was significantly (p<0.05) higher in cancer patients than in noncancer patients. The frequency of beta-lactamase genes in the 58 ESBL-producing P. aeruginosa isolates was determined as 72.41% for blaTEM, 37.93% for blaOXA, 74.14% for blaCTX‐M, and 44.83% for blaSHV genes. The study revealed an alarmingly high prevalence of fecal carriage of ESBL-producing P. aeruginosa with a high rate of MDR among cancer patients. It indicates that regular monitoring and surveillance of ESBL-producing P. aeruginosa among cancer patients are needed to improve the management of patients.